Slow Tumor-Related Spinal Cord Compression, Well-Known Diseases with a Worrying Prognosis: Experience of Dakar - El hadji Cheikh Ndiaye , SY; Hugues Ghislain, Atakla; Wagué, Daouda; Doumbia, Nantenin; Salif Djigo, Richard; Basse, Paul; Salman, Mehsen; Diouf, Ndella Ngoné; BA, Momar Code (Eastern Green Neurosurgery, 2026)
Introduction: Slow spinal cord compression refers to the intra- or extra-medullary development of an expansive lesion in the spinal canal. It represents a diagnostic and therapeutic challenge in our setting, sometimes leading to a poor prognosis. In this study, we examine the epidemiological, diagnostic, and therapeutic aspects of slow spinal cord compression in our setting, while identifying prognostic factors. Patients and Method: This is a retrospective study conducted over a period of six years, from January 1, 2019, to December 31, 2024. It focused on the medical records of 47 patients who were hospitalized in the neurosurgery department of Fann Hospital in Dakar during the study period. Study parameters included epidemiological, diagnostic, histological, therapeutic, and prognostic factors. Results: The average age of our series is 51.06 years, with a predominance of males (63.8%). The time to consultation was greater than 3 months in 78.7% of cases. Neurological examination suggested a picture of slow spinal cord compression, which was confirmed by CT scan in 70.2% of cases and MRI in 78.7%. The predominant location was dorsal (53.19%), followed by dorsolumbar (23.41%) and cervical (23.4%). In this series, 41 patients (87.23%) underwent surgery, while 6 patients (12.77%) did not undergo surgery due to severe deterioration in their clinical condition. Treatment was based on anterior and/or posterior decompression with biopsy or excision, followed by osteosynthesis as indicated. Conclusion: Slow tumor compression of the spinal cord is rare in neurosurgical practice in Dakar. Clinical suspicion leads to imaging, particularly MRI, followed by histological analysis of the surgical specimen. The etiologies are dominated by spinal metastases, and the prognosis is guarded given the late consultations and delayed diagnosis fueled by poverty, cultural convictions, and endogenous beliefs.